Desgin, implementation and control of a single phase inverter - ABU FARHANA NAEL; Ameur, Khaled (Université Amar Telidji- Laghouat FACULTE : TECHNOLOGIE DEPARTEMENT : Département d’Electronique, 2023)
Standalone inverters play a vital role in various applications, such as renewable energy systems, backup power systems, and remote off-grid installations. The purpose of this work is to study, simulate,design and control a single-phase inverter to ensure the stability of the output voltage and carry out experimental test bench at the laboratory. The basic structures and explanation of different types of inverters is presented followed by simulating the global control system using MATLAB/ SIMULINK environment. Explanation of Pulse Width Modulation control techniques and their presented proportional resonant voltage controller and low pass filter is discussed to eliminate low order harmonics.
SPECIALTY: Instrumentation